Essays in the history of Canadian law. - Flaherty, David H. (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2012)
This volume is the second in the Essays in the History of Canadian Law series, designed to illustrate the wide possibilities for research and writing in Canadian legal history. In combination, these volumes reflect the wide-ranging scope of legal history as an intellectual discipline andencourage others to pursue important avenues of inquiry on all aspects of our legal past. Topics include the role of civil courts in Upper Canada; legal education; political corruption;nineteenth-century Canadian rape law; the Toronto Police Court; the Kamloops outlaws and commissions of assize in nineteenth-century British Columbia; private rights and public purposes in Ontario waterways; the origins of workers' compensation in Ontario; and the evolution of the Ontario courts. Contributors include Brendan O'Brien, Peter N. Oliver, William N.T. Wylie, G. Blaine Baker, Paul Romney, Constance B. Backhouse, Paul Craven, Hamar Foster, Jamie Bendickson, R.C.B. Risk, and Margaret A. Banks.